Penyimpangan Moral dalam Kekerasan Seksual di Lembaga Pendidikan: Analisis terhadap Al- Anfal: 27 dan An-Nisa: 135 - Salwa Dama Nazila; Ziyan Yusriana Asri (Yayasan Insan Mulia Bima, 2025)
The phenomenon of sexual violence and harassment in educational institutions is nothing new. However, ironically, religion, which should be a protector, has instead become a shield for the perpetrators, and should uphold moral and spiritual values. From 2020 to 2025, the National Commission on Violence Against Women recorded an increase in the number of reports of sexual violence in religious educational settings, including Islamic boarding schools. Amidst growing public awareness of gender justice and victim protection, abuses of religious authority continue to undermine public trust in religious institutions. From the perspective of the Quran, trustworthiness and justice are fundamental principles that must be upheld by every leader, including religious leaders. Q.S. Al-Anfal: 27 and Q.S. An-Nisa: 135 serve as normative foundations for exposing deviant behavior by some religious scholars, particularly in cases of sexual violence that undermine basic human values. This study aims to analyze the forms of moral deviations committed by religious scholars in cases of sexual violence using an approach to these verses. The method used is a qualitative approach with content analysis techniques. The results of the study indicate that: first, sexual violence in educational institutions is a form of betrayal of the religious and social mandates they hold. And the Qur'anic values ​​of trust and justice must be the benchmark in assessing and responding to cases of sexual violence, as well as being the basis for building collective awareness in rejecting the culture of silence towards victims.